Uji Daya Hambat Filtrat Zat Metabolit Lactobacillus plantarum Terhadap Pertumbuhan Shigella dysenteriae Secara In Vitro - Rizki Putri Andini Rahmah; Meiskha Bahar; Yanti Harjono (Biogenesis: Jurnal Ilmiah Biologi, 2017)
Shigella dysenteriae is pathogenic bacteria causes dysentery diarrhea, a diarrhea with mucus and blood in the feces. Currently, drugs or foods containing Lactobacillus have been circulated in the markets and used by people. This research aims to know the in vitro inhibition test of L. plantarum metabolite substances filtrate against growth of S. dysenteriae. This research used experimental design with L. plantarum metabolite substances filtrate as the samples. Antibacterial test method which was used was the cup-plate technique by looking at clear zone of bacteria’s growth around cup-plate and used Mueller Hinton Agar media. The results showed clear zones on filtrate with concentrations 25%, 50%, 75%, and 100% with average inhibition zones 0,284 cm; 0,332 cm; 0,406 cm; and 0,619 cm. Kruskal-Wallis test results indicated there were significant differences of each filtrate concentration against S. dysenteriae (p<0,05). Post Hoc test showed no significant difference between concentrations 25% and 50% (p>0,05). This suggested lactic acid, acetic acid, and bacteriosin presented in L. plantarum metabolite have antibacterial characteristic